Current Society of Thoracic Surgeons Model Reclassifies Mortality Risk in Patients Undergoing Transcatheter Aortic Valve Replacement. (September 2018) - Kumar, Arnav; Sato, Kimi; Narayanswami, Jyoti; Banerjee, Kinjal; Andress, Krystof; Lokhande, Chetan; Mohananey, Divyanshu; Anumandla, Anil Kumar; Khan, Abdur Rahman; Sawant, Abhishek C.; Menon, Vivek; Krishnaswamy, Amar; et al.
Abstract : Background: The Society of Thoracic Surgeons (STS) scores are used to screen patients for transcatheter aortic valve replacement (TAVR). The STS scores were also used to risk stratify patients in major TAVR trials. This study evaluates the reclassification of predicted risk of mortality by the currently available online STS score calculator compared with the 2008 STS risk model in patients undergoing TAVR. Methods and Results: All patients who underwent TAVR from 2006 to 2016 were included in the study. The STS scores for all included patients were calculated by applying the 2008 STS risk model and again using the current STS online calculator. Among 1209 patients who underwent TAVR, 30-day mortality was 27 (2.2%). The overall predicted risk of mortality estimated by using the current online STS risk calculator was significantly lower than the 2008 STS risk model (6.3±4.4 vs 7.3±4.9; P <0.001). A total of 235 (19%) patients were reclassified into a lower risk category per the current STS risk model. In a multivariable logistic regression analysis, patients with persistent atrial fibrillation (odds ratio, 1.4; 95% CI, 1.0–1.9; P =0.03), chronic heart failure (odds ratio, 6.0; 95% CI, 3.8–10.1; P <0.001), and New York Heart Association class IV heart failure (odds ratio, 2.4; 95% CI, 1.3–4.4; P =0.007) were more likely to be reclassified into a lower risk category per the current STS risk model. Conclusions: The current STS calculation method produces significantly lower predicted risk of mortality than the 2008 calculator, more pronounced in patients with certain comorbid conditions. These results should be considered while evaluating data from prior studies of TAVR.